Theaflavin-3’-O-gallate a Black-tea Constituent Blocked SARS CoV-2 RNA dependant RNA Polymerase Active-site with Better Docking Results than Remdesivir - Banerjee, Amrita; Kanwar, Mehak; Maiti, Smarajit (Drug Research, 2021)
Background Replication of SARS-CoV-2 depends on viral RNA-dependent RNA-polymerase (RdRp). Remdesivir, the broad-spectrum RdRp inhibitor acts as nucleoside-analogues (NAs). Remdesivir has initially been repurposed as a promising drug against SARS-CoV-2 infection with some health hazards like liver damage, allergic reaction, low blood-pressure, and breathing-shortness, throat-swelling. In comparison, theaflavin-3’-O-gallate (TFMG), the abundant black tea component has gained importance in controlling viral infection. TFMG is a non-toxic, non-invasive, antioxidant, anticancer and antiviral molecule.Results Here, we analyzed the inhibitory effect of theaflavin-3’-O-gallate on SARS CoV-2 RdRp in comparison with remdesivir by molecular-docking study. TFMG has been shown more potent in terms of lower Atomic-Contact-Energy (ACE) and higher occupancy of surface area; −393.97 Kcal/mol and 771.90 respectively, favoured with lower desolvation-energy; −9.2 Kcal/mol. TFMG forms more rigid electrostatic and H-bond than remdesivir. TFMG showed strong affinity to RNA primer and template and RNA passage-site of RdRp.Conclusions TFMG can block the catalytic residue, NTP entry site, cation binding site, nsp7-nsp12 junction with binding energy of −6. 72 Kcal/mol with Ki value of 11.79, and interface domain with binding energy of −7.72 and −6.16 Kcal/mol with Ki value of 2.21 and 30.71 µM. And most importantly, TFMG shows antioxidant/anti-inflammatory/antiviral effect on human studies.
Keywords: SARS CoV 2 RdRp; remdesivir; TFMG; Molecular docking; Inhibition